2016
DOI: 10.1016/j.gene.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fam181 gene family during mouse development reveals distinct strain-specific expression patterns, suggesting a role in nervous system development and function

Abstract: During somitogenesis differential gene expression can be observed for so-called cyclic genes, which display expression changes with a periodicity of 120min in the mouse. In screens to identify novel cyclic genes in murine embryos, Fam181b was predicted to be an oscillating gene in the presomitic mesoderm (psm). This gene, and its closely related paralog Fam181a, belong to the thus far uncharacterized Fam181 gene family. Here we describe the expression of Fam181b and Fam181a during murine embryonic development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Although DDIAS functions as an anti-apoptotic protein in response to DNA repair and PRSS23 expression is regulated by estrogens, the other functions of these two genes remain to be elucidated ( Huan et al, 2014 ; Im et al, 2016 ). PRCP and FAM181B may participate in cold adaptation by regulating angiogenesis and nervous system development ( Hagedorn, 2011 ; Marks et al, 2016 ). In addition, ZNF536 , a gene on chromosome 11, showed strong positive selection in the CA chickens, as exhibited by the high F st CA-to-ME , π-Ratio ME/CA , and XPEHH CA-to-ME values ( Figure 5A ), while shared haplotypes were rarely observed in the CA and other chickens ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Although DDIAS functions as an anti-apoptotic protein in response to DNA repair and PRSS23 expression is regulated by estrogens, the other functions of these two genes remain to be elucidated ( Huan et al, 2014 ; Im et al, 2016 ). PRCP and FAM181B may participate in cold adaptation by regulating angiogenesis and nervous system development ( Hagedorn, 2011 ; Marks et al, 2016 ). In addition, ZNF536 , a gene on chromosome 11, showed strong positive selection in the CA chickens, as exhibited by the high F st CA-to-ME , π-Ratio ME/CA , and XPEHH CA-to-ME values ( Figure 5A ), while shared haplotypes were rarely observed in the CA and other chickens ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Some genes ( SLIT1 , TNR , FAM181B , IFT172 , PPM1G , SNX17 , and PREB ) associated with neural development [ 38 , 39 , 40 , 41 , 58 , 59 , 60 , 61 , 62 , 63 ] were also found in the top 20 significant windows for both traits. Costa et al [ 10 ] also detected genes related to neural development that were associated with reproductive traits.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the function of FAM181 proteins; however, one study showed that, in mice, Fam181a/b are expressed in neural tissues, such as the forebrain, midbrain, hindbrain and neural tube. However, knockout of Fam181b does not result in an obvious phenotype (Marks et al, 2016). Therefore, further work is required to determine the role of FAM181A/B in development in order to determine the significance of its interaction with TEAD.…”
Section: )mentioning
confidence: 99%